Role of immunosuppression in an antibiotic stewardship intervention and its association with clinical outcomes and antibiotic use: protocol for an observational study (RISC-sepsis). Issue 12 (9th December 2022) - Scott, Jonathan; Trevi, Loredana; McNeil, Hannah; Ewen, Tom; Mawson, Phil; McDonald, David; Filby, Andrew; Lall, Ranjit; Booth, Katie; Boschman, Gert; Melkebeek, Vesna; Perkins, Gavin; et al.
Abstract : Introduction: Sepsis is characterised by a dysregulated immune response to infection, with exaggerated pro-inflammatory and anti-inflammatory responses. A predominant immunosuppressive profile affecting both innate and adaptive immune responses is associated with increased hospital-acquired infection and reduced infection-free survival. While hospital-acquired infection leads to additional antibiotic use, the role of the immunosuppressive phenotype in guiding complex decisions, such as those affecting antibiotic stewardship, is uncertain. This study is a mechanistic substudy embedded within a multicentre clinical and cost-effectiveness trial of biomarker-guided antibiotic stewardship. This mechanistic study aims to determine the effect of sepsis-associated immunosuppression on the trial outcome measures. Methods and analysis: RISC-sepsis is a prospective, multicentre, exploratory, observational study embedded within the ADAPT-sepsis trial. A subgroup of 180 participants with antibiotics commenced for suspected sepsis, enrolled in the ADAPT-sepsis trial, will be recruited. Blood samples will be collected on alternate days until day 7. At each time point, blood will be collected for flow cytometric analysis into cell preservation tubes. Immunophenotyping will be performed at a central testing hub by flow cytometry. The primary outcome measures are monocyte human leucocyte antigen-DR; neutrophil CD88; programmed cell death-1 on monocytes, neutrophils and T lymphocytes and the percentage of regulatory T cells. Secondary outcome measures will link to trial outcomes from the ADAPT-sepsis trial including antibiotic days; occurrence of hospital-acquired infection and length of ICU-stay and hospital-stay. Ethics and dissemination: Ethical approval has been granted (IRAS 209815) and RISC-sepsis is registered with the ISRCTN (86837685). Study results will be disseminated by peer-reviewed publications, presentations at scientific meetings and via patient and public participation groups and social media.